Effects of liquid property on gas holdup and mass transfer in co-current downflow contacting column - Akosman, C; Orhan, R; Dursun, G (Elsevier Science Sa, 2004)
The effects of liquid property on gas holdup and mass transfer in a co-current downflow contacting column (CDCC) were investigated using air-aqueous glycerol (Analar Reagent, Merck) solutions (AG) with changing the concentration up to 1.5% (w/w). The experiments were conducted using various nozzle diameters at different superficial gas velocities and liquid re-circulation rates. Gas holdup and liquid-side mass transfer coefficient increased with increasing superficial gas velocity and liquid flow rate but decreased with increasing glycerol concentration. The values of gas holdup and mass transfer coefficient in air-aqueous glycerol system were found to be lower than those in air-water system. New correlations for the estimation of gas holdup and mass transfer coefficient in CDCC are proposed. These proposed correlations in terms of liquid kinetic power per liquid volume in the column, superficial gas velocity and relative surface tension fit the experimental data of gas holdup and mass transfer coefficient reasonably well for all gas and liquid flow rates and nozzle diameters used. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: gas holdup; mass transfer; k(L)a; CDCC; liquid property; correlation